Effect of Pre-warmed Intravenous Fluid Therapy on Prevention of Postoperative Shivering after Caesarean Section - Tayebeh Hassan Tehrani; Mohsen Salavati; Mohamad Reza Fazel; Mahmoud Safari; Fatemeh Hasan Shiri; Khodayar Oshvandi (Tehran University of Medical Sciences, 2011)
Background & Aim: Hypothermia is a main side effect during surgery in which blood pressure, heart rate, intra cranial pressure, oxygen consumption, pain and discomfort increase. The rate of cesarean section in Iran is three times more than global standard. This study aimed to investigate effect of pre-warmed intravenous fluid therapy on prevention of shivering after general anesthesia in cesarean section. Methods & Materials: A total of 62 women undergoing general anesthesia for elective cesarean section were randomly allocated into two intervention and control groups. In the intervention group, patients received pre-warmed serum (37°C) and in the control group, patients received serum at room temperature (25.5°C). The postoperative shivering and some homodynamic parameters of the participants were assessed in recovery room. Results: The mean of body temperature in the intervention and control groups were 35.9°C±0.48 and 35.42°C±0.6, respectively (P<0.05). The incidence of post operative shivering in the intervention and control groups were 13% and 35%, respectively (P<0.05). Conclusion: Infusion of pre-warmed serum (37°C) would prevent postoperative shivering and could improve nursing care for women underwent general anesthesia in cesarean section.